2006
DOI: 10.1136/vr.159.4.110
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of magnetic resonance images of granulomatous meningoencephalomyelitis in 11 dogs

Abstract: The characteristics of magnetic resonance imaging (mri) of the brains and spinal cords of 11 dogs with histologically confirmed granulomatous meningoencephalomyelitis (gme) were determined. The lesions were in the brain of eight of the dogs, in the brain and spinal cord of two, and in the spinal cord alone in one dog. A single lesion was present in four of the dogs and multiple lesions were found in six. In one dog with intracranial signs, no visible lesions could be detected on mri. No meningeal enhancement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
112
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 22 publications
9
112
0
3
Order By: Relevance
“…2 The presence of an apparently inflammatory CNS environment in the absence of CSF changes is recognized in the veterinary literature, but the reason for normal CSF remains elusive. [32][33][34] These circumstances make diagnosis challenging and so the availability of other markers of inflammation are of value in these unusual circumstances.…”
mentioning
confidence: 99%
“…2 The presence of an apparently inflammatory CNS environment in the absence of CSF changes is recognized in the veterinary literature, but the reason for normal CSF remains elusive. [32][33][34] These circumstances make diagnosis challenging and so the availability of other markers of inflammation are of value in these unusual circumstances.…”
mentioning
confidence: 99%
“…2). Meningeal enhancement is uncommon (Cherubini et al, 2006). The focal form may be indentified on magnetic resonance imaging or computed-tomography as a non-specific single space-occupying mass lesion (Speciale et al, 1992).…”
Section: Diagnosismentioning
confidence: 99%
“…Several investigators have reported the MRI findings of GME as including isointensity to slight hypointensity on T1W images and hyperintensity on T2W images [3,18]. Only in some cases was enhancement detected on contrastenhanced T1W images [3].…”
mentioning
confidence: 99%
“…Only in some cases was enhancement detected on contrastenhanced T1W images [3]. With regard to the focal form of GME, some studies have reported MRI findings of isointensities on T1W, T2W, and contrast-enhanced images [10,12].…”
mentioning
confidence: 99%